2013
DOI: 10.5301/ejo.5000417
|View full text |Cite
|
Sign up to set email alerts
|

Postcataract Surgery Endophthalmitis after Introduction of the ESCRS Protocol: A 5-year Study

Abstract: Postoperative endophthalmitis is one of the most devastating cataract surgery complications. Our results provide strong evidence of the utility of cefuroxime as prophylaxis of endophthalmitis after cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Among the more recent studies published in 2013, the 6-year incidence of endophthalmitis from the Swedish National Cataract Register (where intracameral cefuroxime is standard) was reported to be 0.029%. 10 In the U.S., a retrospective study that took place at Kaiser Permanente 9 documented a 22-fold decrease in endophthalmitis rates over a 5-year period when intracameral antibiotic injection was routinely used with cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12] Among the more recent studies published in 2013, the 6-year incidence of endophthalmitis from the Swedish National Cataract Register (where intracameral cefuroxime is standard) was reported to be 0.029%. 10 In the U.S., a retrospective study that took place at Kaiser Permanente 9 documented a 22-fold decrease in endophthalmitis rates over a 5-year period when intracameral antibiotic injection was routinely used with cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Both the 2011 American Academy of Ophthalmology (AAO) Cataract Preferred Practice Pattern Guidelines and a 2011 ASCRS Cataract Clinical Committee review of endophthalmitis prevention noted that there was stronger evidence supporting direct intracameral injection than for any other method of antibiotic prophylaxis. 13,14 In 2013, 15 the ESCRS published endophthalmitis prophylaxis guidelines that reviewed the evidence supporting the safety and efficacy of direct intracameral injection of cefuroxime.…”
mentioning
confidence: 99%
“…Worldwide, numerous single-center retrospective analyses have been conducted to examine whether changes in practice patterns resulted in reduced endophthalmitis rates. Several studies have reported reduced rates of endophthalmitis following adoption of intracameral or subconjunctival antibiotics (Beselga 2014; Garat 2009; Garcia-Saenz 2010; Montan 2002; Myneni 2013; Packer 2011; Shorstein 2013). The antibiotic of choice has varied across studies of intracameral injections, with moxifloxacin, vancomycin, and cefuroxime all showing a reduction compared with no antibiotic injection (Packer 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Data from Sweden have shown extremely low rates of postoperative endophthalmitis (0.029%) in the presence of intracameral cefuroxime (Friling 2013). In Portugal, a center found that endophthalmitis decreased from 0.26% to 0.0% after introduction of the ESCRS protocol and use of intracameral cefuroxime (Beselga 2014). Several other studies also have reported declines in endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation